A hierarchical capacitated facility location-allocation model for planning maternal healthcare facilities in India. (May 2022) - Chouksey, Ankit; Agrawal, Anil Kumar; Tanksale, Ajinkya N.
Highlights: Provided a framework for planning maternal healthcare facilities in India. Addressed accessibility and availability issues for proper maternal healthcare. Developed MILP model for capacitated facility location-allocation problem. Proposed valid inequalities and a sequential approach for faster convergence. Applied the framework successfully for a Tehsil in India. Abstract: The present work on maternal healthcare in India is motivated by its current status emerging out of limited availability and accessibility of related facilities. Planning for the required maternal healthcare facilities, from basic ones to neonatal ones, is a tedious task from the financial perspectives of both users and the government. This problem has been addressed by proposing a mixed-integer linear programming formulation for determining the optimal number and location of these capacitated and varied facilities and also for the allocation of mothers-to-be to these facilities while minimizing the overall cost. Suitable additional valid inequalities are proposed to be incorporated into the NP-hard model for reducing the computational burden. For further computational advantage, a sequential approach is also proposed. Comparative performance of the proposed approaches has been analyzed using several problems with wide variation in the problem parameters' values. The sequential approach is found to be very effective and computationally efficient. The results of the sensitivity analyses with respect to coverage distance, capacity, referral proportion and fixed cost provide important and practical insights related to the mix of the facilities to be established. The application of the model for a district in India proves the suitability of the model in the Indian context.